Sistem penilaian kinerja pegawai di kantor Kementerian Agama Provinsi Papua Barat menggunakan metode Self Organizing Map (SOM) - Jubita, Jubita; Suhendra, Christian Dwi; Sanglise, Marlinda (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2024)
A government agency requires employees who have competence and good performance. Various factors affect performance between the abilities of other individuals and the agency environment, including the office of the Ministry of Religion in West Papua Province. However, the performance assessment process still needs to be better for making assessment decisions and is still subjectively based. Those things affect the employee's assessments. For example, employees cannot complete work according to predetermined targets and must be more careful in carrying out the work. So, to facilitate this assessment, an accurate calculation application is needed. A Self Organizing Map (SOM) is used to sort data in a group with similar data that are close to each other. Using the R (programming language) and R studio as the required application platform, we can calculate values and form them into three clusters: very good, quite good, and poor. Then, from the calculation results, 55 employees, with a percentage of 42%, match cluster with quite good performance, 29 employees, with a percentage of 22%, are in cluster with poor performance, and 48 employees, with a percentage of 36%, are in cluster with very good performance.